2006
DOI: 10.1016/j.juro.2006.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Neurokinin-1 Receptor Antagonist in Postmenopausal Women With Overactive Bladder With Urge Urinary Incontinence

Abstract: Results of this initial study suggest that neurokinin-1 receptor antagonism may represent a novel therapeutic approach to treating overactive bladder syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…Various parts of the genitourinary tract, such as the urinary bladder or the kidney, also exhibit neurokinin 1 receptor expression (Meini et al 1994;Chen and Hoover 1995). Application of NK1 receptor antagonists may be effective for the treatment of urge incontinence (Green et al 2006).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…Various parts of the genitourinary tract, such as the urinary bladder or the kidney, also exhibit neurokinin 1 receptor expression (Meini et al 1994;Chen and Hoover 1995). Application of NK1 receptor antagonists may be effective for the treatment of urge incontinence (Green et al 2006).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…Thus, NK-1 receptors could play a key role in a positive feedback, amplification mechanism that enhances sensory input from the bladder and contributes to abnormal reflex bladder activity in guinea pigs. Clinical studies showing that NK-1 antagonists (aprepitant and serlopitant) are effective in treating overactive bladder symptoms (Green et al, 2006;Frenkl et al, 2010) raise the possibility that similar mechanisms exist in humans.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The contribution of NK-1 receptors to the pathophysiology of bladder dysfunction, has attracted the most interest because clinical studies revealed that NK-1 receptor antagonists, aprepitant (Green et al, 2006) and serlopitant (Frenkl et al, 2010), reduce overactive bladder (OAB) symptoms. These agents also reduce normal bladder reflexes in guinea pig, rat, or cat (Doi et al, 1999(Doi et al, , 2000Kamo and Doi, 2001) as well as hyperactive bladder reflexes induced by spinal cord injury (Doi et al, 2000), systemic administration of L-DOPA (Ishizuka et al, 1995), or application of irritant chemicals to the bladder in the rat (Abdel-Gawad et al, 2001) or guinea pig (Doi et al, 1999(Doi et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Aprepitant, an NK-1-receptor antagonist used for treatment of chemotherapy-induced nausea and vomiting (33) significantly improved symptoms of OAB in postmenopausal women with a history of urgency incontinence or mixed incontinence (with predominantly urgency urinary incontinence), as shown in a well-designed pilot randomized controlled trials (34).…”
Section: Pharmacotherapymentioning
confidence: 87%